Largometrajes animados digitalmente en el Perú. Los casos de Red Animation, Origami Studio y Aronnax - Montañez Arica, Jimena del Rosario (2017)
The aim of this research is to analyze the feature film digital animation scene, in the city of Lima, Peru, between the years of 2005-2016. To achieve this, the realization process of the animated movies made in the present, along with its main characteristics and difficulties, is investigated through the study of three different production companies: Origami Studio, Red Animation and Aronnax. The text offers an outlook of the animated movie industry and it divides both their capabilities and their development possibilities.